2020
DOI: 10.1097/htr.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as Potential Biomarkers for Traumatic Brain Injury: Pathway From Diagnosis to Neurorehabilitation

Abstract: Background: Biomarkers that can advance precision neurorehabilitation of the traumatic brain injury (TBI) are needed. MicroRNAs (miRNAs) have biological properties that could make them well suited for playing key roles in differential diagnoses and prognoses and informing likelihood of responsiveness to specific treatments. Objective: To review the evidence of miRNA alterations after TBI and evaluate the state of science relative to potential neurorehabilitation applications of TBI-specific miRNAs. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(197 reference statements)
0
9
0
Order By: Relevance
“…Liu described the increased expression of miR-142-3p, -144, -340-5p, -674-5p, -153, -186, -190, -132*, -138-1*, and decreased let-7b expression in the hippocampus of rats with TBI compared to control [ 30 ]. Herrold’s review presents the results of an analysis of articles about known miRs as a biomarker for diagnosis, natural versus treatment-induced outcomes, and prognosis of TBI [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu described the increased expression of miR-142-3p, -144, -340-5p, -674-5p, -153, -186, -190, -132*, -138-1*, and decreased let-7b expression in the hippocampus of rats with TBI compared to control [ 30 ]. Herrold’s review presents the results of an analysis of articles about known miRs as a biomarker for diagnosis, natural versus treatment-induced outcomes, and prognosis of TBI [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…t-tau levels are elevated at various injury severities 174,203 , and in association with DAI 83,216 , as early as 1 hour after TBI and correlated with positive findings on CT 185,217 , as well as self-reported symptoms after mild TBI 66 . Micro RNA (miRNAs) are small molecules that contribute to gene expression regulation, blood, CSF and brain tissue levels 184,189,[218][219][220][221][222] . It has been demonstrated that miRNA expression is altered across all TBI severities over time periods ranging from 1 hour to several days posttrauma 184,223,224 .…”
Section: 1mentioning
confidence: 99%
“…Micro RNA (miRNAs) are small molecules that contribute to gene expression regulation, blood, CSF and brain tissue levels [184] , [189] , [218] [222] . It has been demonstrated that miRNA expression is altered across all TBI severities over time periods ranging from 1 hour to several days post-trauma [184] , [223] , [224] .…”
Section: Chemical Responses To Tbimentioning
confidence: 99%
“…71 Recently, attention has been given to the potential utility of measuring differential microRNA expression in the diagnosis of TBI, particularly in its role as a protein regulator. 72 Regarding diagnosis of TBI itself, none of these biomarkers has been sufficiently validated to justify its use as a diagnostic tool in the individual case. Key limitations to the individual diagnostic application include (1) a lack of "normative" values of these biomarker candidates in healthy (uninjured) people, (2) the fact that injuries outside the brain/central nervous system (eg, orthopedic trauma) can contribute to circulating plasma or serum concentrations, (3) a lack of standardization or availability of assays timed to expected biomarker elevations, and (4) variability in the definition of TBI.…”
Section: Fluid Biomarkersmentioning
confidence: 99%